The Determination of Superior Food Crop Commodities in West Muna Regency - Hamrin Hamrin; Lukman Yunus; La Ode Alwi (Jurnal Ilmiah Membangun Desa dan Pertanian, 2023)
Food crop commodities have a role in fulfilling the need for food, feed, and domestic industry, so the development of the food crop sub-sector must be prioritized because it has competitive competitiveness. This study aims to determine the superior commodities of food crops in West Muna Regency by specifying the research's location purposively because the area can be developed for various types of food crops. The research data was obtained from the relevant agencies, namely the Agriculture Service and the Office of the West Muna Regency Statistics Agency, in 2016-2020. The data obtained were analyzed using the Location Quotient formula. The study results indicate that peanuts have an LQ value >1 compared to other food crops such as corn, rice, cassava, sweet potatoes, and soybeans. The research can be concluded that the type of food plant in the form of peanuts has the potential to be developed in Muna Regency, as seen from the value LQ>1. West Muna Regency government, in terms of the food crop sub-sector, that to make peanuts a plant with solid competitiveness in West Muna Regency, it is deemed necessary to take various development strategies that are considered feasible for the advancement of superior commodities in West Muna.